Different Methods of Treatment of Patients with Purulent Surgical Diseases of the Hand in Outpatient Settings (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Modern technologies in medicine in the diagnosis and treatment of purulent-inflammatory diseases show positive changes in achieving the success of therapy with such methods as: vacuum treatment of a purulent wound, treatment of a purulent wound with a pulsating jet of liquid, the use of a controlled abacterial medium in the treatment, the use of new antibacterial and dressing agents The proportion of all purulent pathologies of soft tissues and bones of the hand among those who applied for outpatient surgical practice, according to modern authors, ranges from 15% to 30%. Since such diseases are accompanied by both material and social costs, the problem acquires serious medical and social content. During the treatment of patients with purulent surgical diseases of the hand with the traditional method using a 25% solution of dimethyl sulfoxide and levomekol ointment under a gauze bandage, there is a late cleansing of the wound from infection (only by the 5th-6th day of treatment), the onset of granulation by the 7th day of treatment, the onset of epithelialization by the 10th day treatment. Biochemical parameters of wound exudate are normalized only by the 10th day of treatment..